Strategies for COVID-19 Epidemiological Surveillance in India: Overall Policies Till June 2021 - Ghosh, Nimisha; Saha, Indrajit; Sarkar, Jnanendra Prasad; Maulik, Ujjwal (Frontiers in Public Health, 2021)
COVID-19, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has gripped the entire world, almost paralysing the human race in its entirety. The virus rapidly transmits via human-to-human medium resulting in massive increase of COVID-19 patients. In order to curb the spread of the disease, an immediate action of complete lockdown was implemented across globe. India with a population of over 1.3 billion was not an exception and took the challenge to execute phase wise lockdown, unlock and partial lockdown activities. In this work, we intend to summarise these different phases that Government of India imposed to fight against SARS-CoV-2, so that it can act as a reference guideline to help controlling future waves of COVID-19 and similar pandemic situations in India.